STORAGE IS THE MOST INFLUENCING FACTOR OF HOSPITAL SOLID WASTE TREATMENT: SEM ANALYSIS - Alhamda, Syukra; Nurmaya, Ika; Hoa , Dinh Thi Phuong (Universitas Airlangga, 2025)
Introduction: From primary data, it was found that 65% of solid waste generation occurred in 12 hospitals in West Sumatra.